Strategic Planning for a Smart Sustainable City Model: The Importance of Public Administration and Enterprises Cooperation. - Martín-Rojo, Inmaculada Concepción (Palgrave MacMillan, 2024)
In contrast to economistic approaches concerned only with economic profit, a new economy is emerging, whose objective is sustainability - in a broad sense: economic, social, and environmental - and the improvement of people's lives based on collaborative methods, encompassing concepts such as the Economy of the Common Good, Collaborative Economy, Circular Economy, Green Economy, or Blue Economy. This gives rise to new business models that internalize values related to sustainability and Corporate Social Responsibility, but it is not enough for private companies to include these aspects in their strategic approaches; it is also necessary for Public Administrations to act in a socially responsible manner, highlighting the importance of public-private cooperation to achieve sustainable cities. To this we must add the rise of new technologies applied to cities, which gives rise to Smart cities. In this sense, we should not talk about a successful city model, but rather we should first define what kind of city model we want, and then develop strategic planning. In accordance with these approaches, the objective of this chapter is to identify, based on the case studies, the variables to be considered to carry out strategic planning for a Smart Sustainable City model, resilient to future changes and challenges, involving public and private agents.
CAPÍTULO DE LIBRO DEDICADO A ANALIZAR A LO LARGO DE 11 CAPÍTULOS LAS ESTRATEGIAS DE RESPONSABILIDAD SOCIAL CORPORATIVA Y DE SOSTENIBILIDAD DESDE EL ÁMBITO PÚBLICO-PRIVADO https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Planificación estratégica; Desarrollo sostenible; Strategic planning